External Negative Pressure Drainage of the Pancreatic Duct in Pancreatogastrostomy Following Pylorus-Preserving Pancreaticoduodenectomy—Feasibility and Technique - Albrecht, H. C.; Amling, C.; Menenakos, C.; Gretschel, S. (Frontiers in Surgery, 2021)
Background: Postoperative pancreatic fistula (POPF) is a major cause of morbidity after pancreaticoduodenectomy. There is no consensus on the best technique to protect the pancreato-enteric anastomosis and reduce the rate of POPF. This study investigated the feasibility and efficiency of external suction drainage of the pancreatic duct to improve the healing of pancreaticogastrostomy. Methods: Between July 2019 and June 2021, 21 consecutive patients undergoing elective pancreaticoduodenectomy were included. In all patients we performed a pancreaticogastrostomy and inserted a negative pressure drainage into the pancreatic duct. The length and diameter of the pancreatic duct were measured and the texture of the pancreas was evaluated. The daily secretion volume and the lipase value via pancreatic duct drainage were documented. The occurrence of POPF was evaluated. Results: None of the patients had drainage-related complications. In 4 patients we registered a dislocation of the drainage from the pancreas duct into the stomach. 17/21 Patients showed no signs of POPF. A biochemical leak was measured in one patient. Furthermore, 2 patients had a POPF grade B. In one patient, POPF grade C required reoperation and resection of the remnant pancreas. All 4 cases of POPF met the risk criteria soft pancreas, high volume and high lipase value in the duct drainage. Conclusion: The insertion of the pancreatic duct drainage was feasible and caused no drainage-related morbidity. POPF-rate was moderate in the risk population of soft pancreas and small duct.